An analysis of the evolution of mentorship in nursing. Issue 2 (8th May 2018) - Jacobs, Steven
Abstract : Purpose: The purpose of this paper is threefold. First, this paper documents an analysis of mentorship models within the profession of nursing from the 1940s onward. From this analysis, the author was able to categorize the evolution of mentorship models within nursing. Second, this paper identifies four specific contemporary challenges within nursing which relate directly to mentorship. Last, this paper attempts to place a nursing student peer mentorship model in context to best understand how it can benefit the profession of nursing and help address the four identified contemporary challenges within nursing. Design/methodology/approach: The theoretical, philosophical, and research roots that have shaped and informed mentorship models in nursing are examined. The strengths and limitations of nursing mentorship models are analyzed in relation to contemporary challenges in nursing education and practice with a focus on undergraduate peer mentorship. This was achieved through a comprehensive literature review that examined mentorship in nursing from approximately 1940 to the present. Findings: Since Nightingale's time, five specific mentoring models have been created and adapted within the nursing profession. The five mentorship models identified within this paper are most prevalent within current and previous nursing mentorship literature and demonstrate how models within nursing have evolved from those positing a relatively paternalistic relationship to those favoring more collaborative and reciprocal relations between mentor and mentee. Further, it is argued in this paper that a nursing student peer mentorship model can assist in addressing four challenges which currently face the profession of nursing. These four challenges (which are prevalent in nursing literature) are mentoring as a professional responsibility, projected nursing shortages, communication in nursing, and the development of critical thinking skills. Research limitations/implications: A limitation of this paper includes the fact that, despite the many challenges facing the profession of nursing today, this paper focuses on only four identified challenges. As it is impossible for one paper to address all of the contemporary challenges which face nursing today, as articulated below, this paper addresses four identified challenges because they relate to mentorship, nursing education, and nursing practice. Practical implications: Providing opportunities for nursing students to participate in a peer mentoring relationship assists future nurses and the profession as a whole by generating tangible benefits. These benefits include an exposure to theories and models of mentorship and skills to help them fulfill their future professional responsibility of mentoring, development of relationships and skills that can increase both nurse and student retention, and improved communication and critical thinking skills. Last, this study can help nursing schools to identify and work with theories and models of mentorship that will improve their ability to stimulate critical thinking among their students. Originality/value: This paper fills a gap in the literature by providing an analysis of the theoretical, philosophical, and research roots that have shaped and informed mentorship models in nursing from the 1940s onward. This analysis suggests that student peer mentorship may be the most effective model to address these four challenges in nursing: mentoring as a professional responsibility, projected nursing shortages, communication in nursing, and the development of critical thinking skills. This paper has the potential to make a timely contribution to the global debate regarding mentoring across the healthcare professions.